2019
DOI: 10.3899/jrheum.180496
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes over a Short Period Are Associated with Functional Assessments in Rheumatoid Arthritis

Abstract: Objective.To investigate the correlation between changes in radiological quantitative assessment with changes in clinical and functional assessment from baseline to 3 months in patients with rheumatoid arthritis (RA).Methods.Twenty-eight patients with RA [methotrexate (MTX) and anti-tumor necrosis factor–α (TNF-α) group with high disease activity (n = 18); and MTX group with low disease activity (n = 10)] underwent assessments at baseline and 3 months: clinical [28-joint count Disease Activity Score (DAS28)], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Our results were consistent with the results reported previously. 24,25 There are several metrics such as DAS28-ESR, DAS28-CRP, clinical disease activity index and simplified disease activity index etc. for scoring the clinical disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with the results reported previously. 24,25 There are several metrics such as DAS28-ESR, DAS28-CRP, clinical disease activity index and simplified disease activity index etc. for scoring the clinical disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Erosions are most abundant in patients with RA (3,4,16,33,52,54,55,57,64,65,69), especially ACPA and rheumatoid factor (RF) positive RA patients (26). The erosions exhibit a clear predilection for the radial and ulnar quadrant of the 2nd and 3rd MCP joints.…”
Section: Erosion Detection By Hr-pqctmentioning
confidence: 99%
“…Fifteen studies have reported longitudinal changes in the number and/or size of erosions. Of these, three investigated PsA (14,49,66), 10 investigated patients with RA (6,10,15,29,42,46,58,59,64,65), and one study examined ACPA+ individuals without arthritis (62). Seven studies investigated intervention with different therapies either as an open-label study or secondary analysis in a randomized controlled trial.…”
Section: Longitudinal Changes Of the Pathological Measuresmentioning
confidence: 99%
See 2 more Smart Citations